PENGARUH PENYULUHAN KESEHATAN MODEL PEER GROUP TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG TUBERKULOSIS PARU - Rentawati Purba; Yusni Ferabetty (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2018)
Peer groups are teenagers who are equal to the same age and maturity level as well as a place to socialize. One of the problem in adolescence is the lack of knowledge and attitude towards pulmonary TB disease. Purpose of this research to know influence of health counseling peer group model to knowledge and attitude of adolescent about pulmonary TB, type of quasi experimental research, using a comparison group given intervention with non- intervention. This research process has been carried out in april- june 2017 at YP Senior High School Singosari Deli Tua Regency Deli Serdang by method simple random sampling. The number of samples is 76 (38 respondents of intervention group and 38 respondents of non-intervention group). The result showed there was a significant difference (p<0,05) the average value of knowledge and attitudes of adolescents in the intervention and non-intervention groups. This conclusion shows that there is influence of health counseling peer group model to knowledge and attitude of adolescent about pulmonary TB at YP Senior High School Singosari Deli Tua Regency DeliSerdang.